2002
DOI: 10.1002/jnr.10139
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of ansamycins on inducible nitric oxide synthase expression and the development of experimental autoimmune encephalomyelitis

Abstract: The production of nitric oxide by the inflammatory isoform of nitric oxide synthase (NOS2) in brain glial cells is thought to contribute to the causes and development of neurological diseases and trauma. We previously demonstrated that activation of a heat shock response (HSR) by hyperthermia reduced NOS2 expression in vitro, and in vivo attenuated the clinical and histological symptoms of the demyelinating disease experimental autoimmune encephalomyelitis (EAE; Heneka et al. [2001] J. Neurochem. 77:568-579). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 48 publications
(60 reference statements)
3
30
0
2
Order By: Relevance
“…14 As 17AAG has less toxicity and higher selectivity for client proteins, 17AAG is the first Hsp90 inhibitor to enter clinical trials. Other than the cancer area, Hsp90 inhibitors have also been shown to be effective as neuroprotective agents in animal models of Parkinson disease, 17 stroke, 18 autoimmune encephalitis, 19 and spinal and bulbar muscular atrophy. 20 In this study, we have shown the efficacy of 17AAG in tubulointerstitial fibrosis induced by UUO, and considerably extended the therapeutic application of 17AAG beyond cancer and inflammatory and degenerative diseases.…”
Section: Hsp90 Inhibitor Reduces Renal Fibrosis H Noh Et Almentioning
confidence: 99%
“…14 As 17AAG has less toxicity and higher selectivity for client proteins, 17AAG is the first Hsp90 inhibitor to enter clinical trials. Other than the cancer area, Hsp90 inhibitors have also been shown to be effective as neuroprotective agents in animal models of Parkinson disease, 17 stroke, 18 autoimmune encephalitis, 19 and spinal and bulbar muscular atrophy. 20 In this study, we have shown the efficacy of 17AAG in tubulointerstitial fibrosis induced by UUO, and considerably extended the therapeutic application of 17AAG beyond cancer and inflammatory and degenerative diseases.…”
Section: Hsp90 Inhibitor Reduces Renal Fibrosis H Noh Et Almentioning
confidence: 99%
“…[18,25] . 格尔德霉素具有 抗肿瘤、抗菌、抗原虫、抗病毒、抗炎、免疫调节和调 节上皮氮氧合酶活性 [25,26] , 报道最多的是抗肿瘤活性, 且作用靶点为 Hsp90; 但格尔德霉素有较强的肝脏毒性 和较差的水溶性, 生物利用度也不高, 研究者也在不断 寻找新的格尔德霉素的衍生物 [26] , 如 17-位甲氧基被烯 丙氨基取代的 17-AAG 已进入临床 II 期 [27] . 尼日利亚菌 素具有抗菌、抗肿瘤、抗病毒、抗疟原虫以及抗疟疾等 活性 [17,28] , 在农业生产中用于治疗鸡球虫病以及牲畜生 长促进剂 [17] ; 但有关尼日利亚菌素的抗肿瘤活性的报 道较少, 仅有抗上皮肿瘤干细胞和肺癌细胞 DLKP-A10 的两篇报道 [29,30] .…”
Section: 菌株鉴定结果unclassified
“…Aging is also known to result in over-expression of HSP-70i [45] that in turn desensitizes Ca 2+ machinery and turns off new synthesis of HSP-70i [46][47][48]. Bioflavonoid such as quercetin prevents HSF1 binding to HSEs, thereby leading to attenuation of HSP-70i gene expression [49].…”
Section: Protein Regulation Of Hsp-70imentioning
confidence: 99%
“…Both geldanamycin and 17-allylamino-17-demethoxygeldanamycin, members of the ansamycin family, have been demonstrated to reduce NO production, iNOS mRNA, and cytokine-induced activation of the iNOS gene promoter in cultured cells [49], in rats [6], and in mice [13].…”
Section: Down-regualtion Of Inosmentioning
confidence: 99%